1960
DOI: 10.1084/jem.112.4.581
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Cell-Virus Relationship

Abstract: HeLa cell cultures have been reported previously to be resistant to infection by Coxsackie A9 virus (1, 2). Similar results have been reported for a number of other stable cell strains derived from human tissues (3-6). In contrast, this virus has been reported to infect primary cell cultures of human and monkey cells (1,3,(7)(8)(9). The resistance of HeLa cells to A9 virus infection was shown by Takemoto and Habel (10) to be relative, since virus-carrier cultures could be produced. Even in the presence of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…McLaren, Holland and Syverton (1960) reported that the resistance of HeLa cells to CA 9 virus infection is correlated with the absence of the receptor active in the primary adsorption of this virus. Takemoto and Habel (1959) showed that the resistance of HeLa cells to CA 9 virus infection was relative, since virus carrier cultures could be established and even when a relatively large amount of virus was present, only a small proportion of the cells was infected at any time.…”
Section: Introductionmentioning
confidence: 99%
“…McLaren, Holland and Syverton (1960) reported that the resistance of HeLa cells to CA 9 virus infection is correlated with the absence of the receptor active in the primary adsorption of this virus. Takemoto and Habel (1959) showed that the resistance of HeLa cells to CA 9 virus infection was relative, since virus carrier cultures could be established and even when a relatively large amount of virus was present, only a small proportion of the cells was infected at any time.…”
Section: Introductionmentioning
confidence: 99%